Demonstrating grating-based phase-contrast imaging of laser-driven shock waves - Wegert, Leonard; Schreiner, Stephan; Rauch, Constantin; Albertazzi, Bruno; Bleuel, Paulina; Fröjdh, Eric; Koenig, Michel; Ludwig, Veronika; Martynenko, Artem S.; Meyer, Pascal; Mozzanica, Aldo; Müller, Michael; et al. (Matter and Radiation at Extremes, 2024)
Single-shot X-ray phase-contrast imaging is used to take high-resolution images of laser-driven strong shock waves. Employing a two-grating Talbot interferometer, we successfully acquire standard absorption, differential phase-contrast, and dark-field images of the shocked target. Good agreement is demonstrated between experimental data and the results of two-dimensional radiation hydrodynamics simulations of the laser-plasma interaction. The main sources of image noise are identified through a thorough assessment of the interferometer’s performance. The acquired images demonstrate that grating-based phase-contrast imaging is a powerful diagnostic tool for high-energy-density science. In addition, we make a novel attempt at using the dark-field image as a signal modality of Talbot interferometry to identify the microstructure of a foam target.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Electromagnetic pulse; Gratings; Interferometry; Phase contrast microscopy; X-ray imaging; X-ray phase contrast imaging; Lasers; Shock waves; Hydrodynamics simulations

Design of a Talbot phase-contrast microscopy imaging system with a digital detector for laser-driven X-ray backlighter sources - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Fröjdh, Erik; Ludwig, Veronika; Martynenko, Artem S.; Meyer, Pascal; Mozzanica, Aldo; Müller, Maximilian; Neumayer, Paul; Schuster, Max; et al. (Journal of Instrumentation, 2024)
Laser-driven shock waves in matter propagate with multiple kilometers per second and therefore require sources like a laser-driven backlighter, which emit the X-rays within picoseconds, to be able to capture sharp images. The small spatial extent of shocks in low-density materials pose challenges on the imaging setup. In this work, we present a design process for a single-shot X-ray phase-contrast imaging system geared towards these objects, consisting of a two-grating Talbot interferometer and a digital X-ray detector. This imaging system is optimized with respect to the detectable refraction angle of the X-rays induced by an object, which implies a high phase sensitivity. Therefore, an optimization parameter is defined that considers experimental constraints such as the limited number of photons, the required magnification, the size and spectrum of the X-ray source, and the visibility of the moiré fringes. In this way, a large parameter space is sampled and a suitable imaging system is chosen. During a campaign at the PHELIX high-power laser facility a static test sample was imaged which is used to benchmark the optimization process and the imaging system under real conditions. The results show good agreement with the predicted performance, which demonstrates the reliability of the presented design process. Likewise, the process can be adapted to other types of laser experiments or X-ray sources and is not limited to the application presented here.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Inspection with x-rays; Models and simulations; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

Electromagnetic pulse protective shielding for digital x-ray detectors - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Fröjdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
Laser-driven x-ray backlighting can be used to image fast dynamic processes like the propagation of laser-driven shock waves in matter. We demonstrate and evaluate the feasibility of operating the JUNGFRAU detector designed by PSI, a direct detecting x-ray detector, in environments with extreme electromagnetic pulses. The electromagnetic pulse-protective housing is specifically designed for this detector and optimized for pump-probe experiments at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) facility at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. The beryllium x-ray entrance window of the protective housing has a high x-ray transmission of 94% at 8 keV. Measurements have shown that the housing simultaneously provides a relative damping of the electromagnetic field on average higher than 1000 in the frequency range of 100 MHz to 5 GHz. The results demonstrate the feasibility of operating digital detectors in experiments where strong electromagnetic pulses are present.
CRIS-Team Scopus Importer:2023-08-11

Erratum: Publisher's Note: "Electromagnetic pulse protective shielding for digital x-ray detectors" [Rev. Sci. Instrum. 94, 075106 (2023) (The Review of scientific instruments (2023) 94 7 PII: 089902) - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Frojdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
CRIS-Team Scopus Importer:2023-12-22

Stabilizing high aspect ratio x-ray gratings with top layer resist grid - Richter, Michael; Beckenbach, Thomas; Rauch, Constantin; Schreiner, Stephan; Zuber, Marcus; Hamann, Elias; Last, Arndt; Börner, Martin; Korvink, Jan; Meyer, Pascal (Journal of Micro-Nanolithography MEMS and MOEMS, 2024)
A problem with high aspect ratio x-ray gratings, fabricated by the deep x-ray LIGA process, is the collapse of the metallic structure when the resist is removed. A unique method that consists of positioning perpendicular metal bridges on top of the grating (roof bridges) is described and tested as a solution. First, a theoretical study is carried out on the transmission loss of such grids as a function of the thickness, their spacing, their materials (gold or nickel), and the x-ray energy. Different processes with their own advantages and disadvantages are possible and described. To further satisfy the requirement of curved gratings, two processes are tested in detail: structuring the x-ray grating with a laser and planarization followed by restructuring a second resist layer. In both cases, a second electroplating step is performed. Finally, a grating with a 12 cm bending radius and stabilization is fabricated. To assess the quality of the grids, two complementary methods are used: scanning electron microscopy and angular x-ray transmission. The latter one is an innovatively developed measurement process specially dedicated to x-ray gratings. The results for the fabrication processes are discussed and rated. The stability provided by the roof bridges works as intended, although the overall quality of the grating is slightly reduced.
CRIS-Team Scopus Importer:2024-04-12
Keywords: angular x-ray transmission; Talbot–Lau interferometry; x-ray grating; x-ray LIGA

X-ray Dark-Field Imaging for Improved Contrast in Historical Handwritten Literature - Akstaller, Bernhard; Schreiner, Stephan; Dietrich, Lou; Rauch, Constantin; Schuster, Max; Ludwig, Veronika; Hofmann-Randall, Christina; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2022)
If ancient documents are too fragile to be opened, X-ray imaging can be used to recover the content non-destructively. As an extension to conventional attenuation imaging, dark-field imaging provides access to microscopic structural object information, which can be especially advantageous for materials with weak attenuation contrast, such as certain metal-free inks in paper. With cotton paper and different self-made inks based on authentic recipes, we produced test samples for attenuation and dark-field imaging at a metal-jet X-ray source. The resulting images show letters written in metal-free ink that were recovered via grating-based dark-field imaging. Without the need for synchrotron-like beam quality, these results set the ground for a mobile dark-field imaging setup that could be brought to a library for document scanning, avoiding long transport routes for valuable historic documents.
CRIS-Team Scopus Importer:2022-10-07
Keywords: cultural heritage; grating-based phase-contrast imaging; X-ray dark-field imaging